1999
DOI: 10.1074/jbc.274.12.8328
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferators Enhance Cyclooxygenase-2 Expression in Epithelial Cells

Abstract: The formation of prostaglandins requires the catalytic activity of cyclooxygenase (COX) which converts arachidonic acid to the prostaglandin endoperoxide PGH 2 , from which all other prostaglandins are formed. COX-2 is the highly inducible isozyme of COX which is responsible for much of the prostaglandin production in inflammation and is a key factor in colon carcinogenesis. Because COX-2 activity can be rate-limiting in prostaglandin formation, COX-2 expression must be regulated tightly. Numerous factors, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
183
1
5

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(202 citation statements)
references
References 38 publications
13
183
1
5
Order By: Relevance
“…A previous study demonstrated that COX-2 contains a PPRE in the promoter region and is a target for PPAR-mediated transactivation in epithelial cells 65 and immortalized keratinocytes 66 . Importantly, COX-2 induction has been implicated in UV-mediated processes ranging from carcinogenesis to local and systemic immunosuppression 29,30,[67][68][69] .…”
Section: Pparγ and Uvrmentioning
confidence: 99%
“…A previous study demonstrated that COX-2 contains a PPRE in the promoter region and is a target for PPAR-mediated transactivation in epithelial cells 65 and immortalized keratinocytes 66 . Importantly, COX-2 induction has been implicated in UV-mediated processes ranging from carcinogenesis to local and systemic immunosuppression 29,30,[67][68][69] .…”
Section: Pparγ and Uvrmentioning
confidence: 99%
“…ulating cyclooxygenase-2 in our systems because inhibitors of cyclooxygenase-2 catalytic activity, including NS-398, themselves induce cyclooxygenase protein expression (12).…”
Section: Figmentioning
confidence: 99%
“…Endothelial cells express cyclooxygenase-2 in response to diverse soluble agonists ranging from serum (32) to endotoxin (8) to cytokines (7,9) to lipid agonists of peroxisome proliferator-activated receptors (12,33). Cyclooxygenase-2 expression has not been characterized as a response to environmental stimuli such as intercellular contacts, although prostaglandin production from arachidonate by endothelial cells is modulated by the number of population doublings (34), and cell density has been shown to affect the amount of PGE 2 made in response to IL-1 stimulation of an osteoblast-like cell line (35).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 expression is increased by various substances including mitogens, 2 tumor promoters, 3,4 cytokines, 1,2,5,6 serum, 5 and free fatty acids. 7 Other studies have shown that COX-2 is also regulated by nonsteroidal antiinflammatory drugs (NSAIDs) or by selective COX-2 inhibitors. [7][8][9][10] COX-2 is expressed in many types of cancers including colon, 11,12 pancreas, 8,13,14 stomach, [15][16][17] lung, 12,18 breast, 12,19 prostate, 20 cervix, 6 head and neck, 21 esophagus, 22 bladder, 23 glioma, 24 and melanomas.…”
mentioning
confidence: 99%